Peroralni pulzirajoči dostavni sistemi - Planinšek, Odon (Farmacevtski vestnik, 2016)
Oral pulsatile drug delivery systems show many superior performance characteristics when compared to other approaches for controlled release. They deliver the right dose of a drug in a burst, followed by periods of no release at the right time and at the right site in the gastrointestinal tract. They are beneficial for active pharmaceutical ingredients with chro nopharmacological behavior, and for drugs that show significant first-pass metabolism, local diseases treatment in gastrointestinal tract or improved systemic absorption of active pharmaceutical ingredient in colon. In the article, basic concepts of pulsatile therapeutic systems are introduced, the reasons for their development are explained together with composition and mechanisms of the drug release modification from the appropriate dosage forms.
Keywords: farmacevtski preparati; kronoterapija; mestno specifično sproščanje; nadzorovano sproščanje; peroralne farmacevtske oblike; pulzirajoči terapevtski sistemi